Neurological Emergencies 2019
DOI: 10.1007/978-3-030-28072-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-otologic Emergencies: A Practical Approach

Abstract: Diagnostic Keys• Stroke is an important cause of acute dizziness in the emergency setting.• Small posterior strokes can present with an isolated acute vestibular syndrome. • Physical exam findings often allow for a confident and specific diagnosis and reliably discriminate between peripheral and central disorders. • Early (<48 hours of onset) neuroimaging even with DW-MRI may miss up to 15-20% of posterior circulation strokes presenting as isolated dizziness. • Sudden sensorineural hearing loss (SSNHL) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…One such procedure, the Epley, has a high success rate (85-90%) for posterior semicircular canal BPPV and has no serious consequences other from nausea and vomiting. Studies have shown that symptom recovery rates vary from 50% to 95% following one to two weeks of therapy 7,8 . As a result, most Iranian doctors who treat vertigo only use medicine rather than this alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such procedure, the Epley, has a high success rate (85-90%) for posterior semicircular canal BPPV and has no serious consequences other from nausea and vomiting. Studies have shown that symptom recovery rates vary from 50% to 95% following one to two weeks of therapy 7,8 . As a result, most Iranian doctors who treat vertigo only use medicine rather than this alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of people may only need a single treatment, although there are always exceptions. Several individuals describe continuing discomfort after a successful relocation 7 . Individuals may report feeling unsteady or dizzy without vertigo.…”
Section: Introductionmentioning
confidence: 99%